Self-Assessed Risk of HIV and Other STIs Among Young Adults in Norway and Croatia - Traen, Bente (Array, 2012)
The purpose of the present study is to explore how sexually active young Norwegian and Croatian adults assess the risk of being infected with HIV and other STIs. Study results are based on a 2009–2010 large-scale national probability survey of young adults aged 18–24 in Croatia (n = 1, 005) and Norway (n = 871). A majority of sexually active young adults in Croatia and Norway assessed the risk of becoming infected with HIV or other STIs as low or negligible. Among noncondom users, 85–98% determined they had low or no risk of getting infected with HIV. The corresponding figures for STIs were 77–79%. In both countries a higher HIV risk self-assessment was observed among those who had had same-sex sexual experience, those who reported a higher number of sex partners during the past year, and those who were single. When investigating the patterns of HIV/STI risk assessment, gender and country-related differences appeared. Condom use associated with higher risk assessment was significant only among Croatian men. The strong perception of condom use as being a male responsibility in Croatia may be the reason for a higher risk assessment for unwanted pregnancy and HIV/STIs when protection fails. The risk assessment for HIV/STIs was not associated with partner turnover in Croatian men. New campaigns need to develop gender-sensitive messages, particularly targeting men who believe that a great number of sexual partners is a sign of manliness and women who shy away from their responsibility to use protection.